Research Note: Molecular Subtyping of Salmonella enterica serovar Tshiongwe Recently Isolated in Malaysia During 2001-2002 - Thong, Kwai Lin; Bakeri, Shamsilawani Ahmad; Lai, Kin Seng; Koh, Yin Tee; Taib, Mohd Zainuldin; Lim, V.K.E.; Yasin, Rohani Md (Seameo Regional Tropical Medicine & Public Health, 2004)
Pulsed field gel electrophoresis (PFGE) and antimicrobial susceptibility analysis were undertaken on twenty-three strains of Salmonella enterica serovar Tshiongwe, an unusual serovar, which recently emerged in Malaysia. Antimicrobial susceptibility analysis showed that all the strains were sensitive to ampicilin, chloramphenicol, cotrimoxazole, and kanamycin. Twenty (87) and 8 (3.5) strains had resistance to tetracycline and streptomycin respectively. PFGE analysis subtyped 23 strains into 10 profiles (Dice coefficient of similarity, F = 0.7-1.0). The predominant profile, X1 was found in both clinical and environmental isolates and was widely distributed in different parts of Malaysia during the study period. In addition, isolates recovered from food, a hand-towel, apron and the surface of a table-top in one particular location had unique, indistinguishable profiles (X4/4a) and identical antibiograms. Similarly, isolates from cooked meat and a chopping board had PFGE profiles similar to some human isolates. These probably indicated cross-contamination and poor hygiene in food practices, hence contributing to Salmonellosis. Factors causing the emergence of this rare Salmonella serovar being responsible for food poisoning episodes during the study period remained unclear. The study reiterated the usefulness and versatility of PFGE in the molecular subtyping of this rare Salmonella serovar in Malaysia.